2019
DOI: 10.1039/c9tb00665f
|View full text |Cite
|
Sign up to set email alerts
|

Development of Gold-PAGE: towards the electrophoretic analysis of sulphurous biopolymers

Abstract: Gold nanoparticles, encapsulated within polyacrylamide electrophoresis gels, can discriminate between number of type of sulphur modifications in DNA strands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…85 The use of human SA as drug carrier is based on the fact that SA is an important carrier of endogenous and exogenous hydrophobic molecules in the human circulation. 138 Studies have demonstrated that the SA-bound paclitaxel formulation differs favorably from unbound paclitaxel in terms of tumor accumulation of SA, patient toleration, response rate, and extends the time to tumor progression. 139 Besides Abraxane, an active-targeted NP, Rexin-G, is commercially available outside of the USA (Table 1) and there are other drug nanocarriers that incorporate an active targeting ligand in clinical trials (eg, HA-Irinotecan in phase III and RGD-PET-CT in phase II).…”
Section: Lectinsmentioning
confidence: 99%
“…85 The use of human SA as drug carrier is based on the fact that SA is an important carrier of endogenous and exogenous hydrophobic molecules in the human circulation. 138 Studies have demonstrated that the SA-bound paclitaxel formulation differs favorably from unbound paclitaxel in terms of tumor accumulation of SA, patient toleration, response rate, and extends the time to tumor progression. 139 Besides Abraxane, an active-targeted NP, Rexin-G, is commercially available outside of the USA (Table 1) and there are other drug nanocarriers that incorporate an active targeting ligand in clinical trials (eg, HA-Irinotecan in phase III and RGD-PET-CT in phase II).…”
Section: Lectinsmentioning
confidence: 99%